(untitled) (ModaPalavra e-periódico, 2008)
The social contemporary processes emphasize the complexity of constitution conditions and the individual and collective identities conceptions, making to proliferate, in a quick pace, unlimited situations, experiences and stimulations. The citzen who rises out from these proccesses is marked of possibilities, mutant and manager of different identities. The clothes fashion is one of the components of social conditions of indentity subjectivization and construction, establishing a net of relations with these citizens of possibilities. The clothes and the body compose subjectivities creating and expressing images and forms those correspond to the identifications and differentiations from where the identities emerge. The instantaneity of these changes does not allow that old identities are demolished, coexisting with the new ones. Fashion imposes standards at the same time it allows distinction between people and social groups and in this way it promotes a permanent recreation of the citizens always in devir. The diversity of styles does not eliminate the differentiation of the brands.